Assessment of the influence of Nutri-Score on Polish consumer Choices - Insights from the nationwide, Cross-sectional study - Hubert Dobrowolski; Dariusz Włodarek; Mariusz Panczyk (Scientific Reports)
Abstract The public is increasingly looking for healthier alternatives in food products. Front-of-pack labelling aims to help consumers make healthier food choices. The aim of our study was to investigate whether Nutri-Score can improve nutritional choices of Polish consumers. The survey was conducted using the CAWI method. The proprietary questionnaire included metric questions, knowledge about the Nutri-Score system and questions on nutritional knowledge from the KomPAN questionnaire. To assess the effectiveness of the Nutri-Score system, participants compared healthiness of 8 product pairs with visible and invisible Nutri-Score labelling. The study involved 1035 participants, a representative sample of the Polish population. Participants had average nutritional knowledge (5.6 ± 2.14 out of 10 points) and average knowledge of Nutri-Score (2.9 ± 1.66 out of 7 points). The results showed that visibility of the system did not significantly (p > 0.05) influence consumers’ dietary choices. An unfavourable dietary change was shown (p < 0.001) for two pairs of products: fish (OR of 11.56 (95% CI [8.40–15.91]) and ham OR of 2.84 (95% CI [2.19–3.69]). The distribution of the data obtained indicated a negative effect of the system on consumer choices. In conclusion, our study showed that the Nutri-Score system has a limited effect on improving health-promoting dietary choices.